[A.I.D.S. ; Baguio Baby ; Solar energy [videorecording] (Quezon City Probe Productions, 1992)
An interview with persons with AIDS. Takes a look into the second reported case of a newborn baby being kidnapped in Baguio General Hospital and into the program to supply solar energy panels at low costs by the National Electrification Administration.
A.I.D.S. (18 min.) -- Baguio Baby (12 min.) -- Solar energy (11 min.)
VHS.
Keywords: AIDS (Disease) -- Patients -- Philippines; Kidnapping -- Philippines -- Baguio City; Solar energy -- Philippines -- Sto. Tomas (Iloilo)